Translational requirement for La Crosse virus S-mRNA synthesis: a possible mechanism. - Bellocq, C (1987)
Ongoing protein synthesis is required for La Crosse S-mRNA synthesis in vivo, and complete S-mRNA can be made in vitro only in the presence of an active rabbit reticulocyte lysate. Using in vitro systems based on the polymerase activity of purified virions, we further support the notion that it is translation of the nascent mRNA that is required for complete transcription. Since replacement of guanosine with inosine in the nascent mRNA substitutes for the translational requirement, it appears that translation is required to prevent interactions of the nascent chain from taking place, which, if not prevented, lead to premature termination. These interactions appear to be between the nascent mRNA chain and its nucleocapsid template. A model for the translational requirement for complete S-mRNA synthesis is presented.